Surgical treatment of the floppy eyelid syndrome - I. A. Filatova; Yu. P. Kondratieva; I. M. Mohammad; S. A. Shemetov; A. M. Maybogin (Российский офтальмологический журнал, 2023)
Purpose: to evaluate the effectiveness of surgical treatment of the floppy eyelid syndrome. Material and methods. The clinical group consisted of 23 patients (46 eyes) with the floppy eyelid syndrome (16 men and 4 women), ave. aged 46,0 ± 2.6 years. Of these 20 patients underwent surgery for floppy eyelid syndrome by vertical and horizontal shortening of the upper eyelid with or without correction of blepharoptosis. The observation period ranged from 1 month to 10 years. Fragments resected during the operation were subjected to histological examination. Results. A histological study revealed a reduced quantity or absence of elastin in the tarsal plate, destruction of collagen fiber beams, malformation of hair follicles accompanied by moderate chronic inflammation, In the postoperative period, the complaints caused by involuntary ectropion of the upper eyelid disappeared in all patients, the palpebral fissures became maximally symmetric. Conclusion. Surgeries performed by our technologies result in the best possible anatomical arrangement of the upper eyelid within a single-stage procedure.